Pendekatan Filsafat dalam Studi Islam di Era Moderen: Relevansi dan Tantangan Gaya Hidup Generasi Z (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
This study aims to analyze the relevance of philosophical approaches in Islamic studies to the challenges of Generation Z lifestyle in the modern era, as well as to identify strategies for implementing Islamic philosophical values in contemporary digital life. Generation Z faces a dilemma between maintaining Islamic identity and meeting the demands of modernity that often conflict with religious principles. This research employs a qualitative method with a descriptive approach based on library research. The research sample consists of literature relevant to the research theme, including academic books, scientific journal articles, and digital content discussing Islamic philosophy, Generation Z characteristics, and modernity issues. The research instrument uses systematic literature selection techniques with criteria of thematic relevance, social and philosophical context relevance, and thematic continuity related to Islamic philosophy and Generation Z lifestyle. Data analysis is conducted through data source triangulation to ensure validity and objectivity of findings. The research results show that Islamic philosophical approaches, particularly the concepts of tawhid, Islamic epistemology (integration of naqli and aqli knowledge), Islamic ethics, and theology, have high relevance in helping Generation Z face modern lifestyle challenges. The discussion reveals three main aspects: Generation Z challenges in the digital context include social alienation, value conflicts, and critical attitudes toward religious institutions; the relevance of Islamic philosophy lies in its ability to integrate rationality and spirituality; and strategies for facing modernity through the unification of revelation and reasoning, strengthening Islamic ethics in the digital world, and understanding Islamic metaphysics. The research conclusion affirms that Islamic philosophy provides a framework of thought that can guide Generation Z to maintain their Islamic identity while adapting to the demands of the times, enabling them to live a balanced life between spirituality and modernity.